(untitled) (Research, Society and Development, 2022)
Background/objective: This study is a systematic review and meta-analysis that aims to systematize and synthesize the results of observational studies which demonstrated the occupational stress influence in workers’ health. Methods: The literature review was carried out through searches in PUBMED, WEB OF SCIENCE, EMBASE, SCOPUS, CINAHL, PSCYINFO, and LILACS databases, from July to October 2020, and updated in October 2021. Observational studies that considered occupational stress as exposure, accessed it by the Job Content Questionnaire, and evaluated its influence in workers’ health were included, regardless of their publication year. The risk of bias of the included studies was assessed through the Research Triangle Institute Item Bank on Risk of Bias and Precision of Observational Studies. Results: For the qualitative analysis, the search strategy retained 42 studies, including 182187 participants. Among retained studies, the influence of occupational stress was examined in cardiovascular diseases (CVD) (n=10), as primary outcome, and metabolic syndrome (MS) (n=5), dyslipidemias (n=15), and obesity (n=22), as additional outcomes. Systematized evidence showed that high levels of occupational stress appear to be associated with CVD and MS. However, its influence in dyslipidemias and obesity remain unclear. Meta-analyses of these clinical conditions showed significant associations between occupational stress and CVD (OR 1.34; 95%CI 1.15-1.57) and MS (OR 2.75, CI95% 1.97-3.83), but no significant effect between stress at work and dyslipidemias and obesity. Conclusions: A consistent adverse effect of occupational stress was observed on CVD and MS, considering studies with high methodological quality (low risk of bias). These findings can contribute to the development of actions to attenuate the stress at work to provide a better quality of life for workers. Other: This work received no specific grant from any funding agency and was registered on the PROSPERO platform under the CDR protocol number 102751.